Analisis mitigasi risiko pada akad mudharabah dan murabahah perbankan syariah: perbankan syariah - Aini, Adinda Putri Nur (Maliki Interdisciplinary Journal, 2023)
This study aims to analyze risk mitigation on mudharabah and murabaha contracts in Islamic banking. This study uses a qualitative approach in the form of a literature review with the aim of describing the problem under study. Data collection techniques with literature studies originating from various sources such as the internet, books, research journals that have the same topic. The results of the study are that Mudharabah is a form of cooperation which currently faces many development constraints such that shahibul mal uses a contract system that refers to PBI 13/23/PBI/2011 concerning Risk Management and Sharia Commercial Banks in sharia business entities there are ten risks that must be addressed. managed by OJK regulation number 65/PJOK 03/2016 concerning the application of risk management for Islamic Commercial Banks and Sharia Business Units.